COST-VOLUME-PROFIT ANALYSIS AS A TOOL FOR EVALUATING THE ACHIEVEMENT OF PROFIT ON GULAKU PRODUCT IN MINI MARKET PRIMER KOPERASI MARKAS BESAR ANGKATAN UDARA BEFORE AND DURING COVID-19 PANDEMIC - Laura Magdalena Tampubolon; Juaniva Sidharta; Lumbantoruan , Rutman (Universitas Kristen Indonesia, 2022)
The COVID-19 pandemic has the potential to result in losses on profit achievement, including Gulaku products at the Mini Market Primer Koperasi Markas Besar Angkatan Udara (Mini Market Primkopau), especially when the emergence of this virus in early 2020. Good profit achievement is evaluated not only from the nominal profit alone, but using tools such as cost-volume-profit analysis, namely the break-even point and safety limit. Therefore, this study aims to determine profit achievement, find out cost-volume-profit analysis, and find out the results of cost-volume-profit analysis as an evaluation tool for achieving profit on Gulaku Products at the Mini Market Primer Koperasi Markas Besar Angkatan Udara Before and During the COVID-19 Pandemic. The research focused on the differentiation of Gulaku Hijau and Gulaku Kuning products in the research period before and during COVID-19, namely 2019, 2020, and 2021. Based on the evaluation that has been carried out, it can be seen that the COVID-19 pandemic has affected the profit achievement of Gulaku products in the Mini Market Primkopau. Despite experiencing a decline in profit achievement in 2020, Primkopau still managed to break even. In addition to the COVID-19 pandemic, it turns out that other behaviors have an influence on the achievement of Gulaku product profits, namely large demand switching to Gulaku Kuning which causes a significant decrease in the achievement of Gulaku Hijau profits and a significant increase in the Gulaku Kuning profit achievement followed by the product mix in 2021 Keywords : CVP Analysis, profit achievement, COVID-19